Analisis Akuntabilitas Dan Transparansi Pengelolaan Pendapatan Objek Wisata Gunung Kawi Desa Sebatu - Erlina Yanti, Ni Ketut; Putra, I Made Endra Lesmana; Pratiwi , Ni Putu Trisna Windika (Hita Akuntansi dan Keuangan, 2024)
Management of revenue from the Gunung Kawi Tourism Object in Sebatu Village, the transparency process is not good. The revenue management of the Gunung Kawi Sebatu tourist attraction has government involvement in revenue management which is good. Participatory management of the income of the Gunung Kawi Tourism Object in Sebatu Village has been carried out, namely there is community involvement in the receipt and utilization of income. Transparency in managing the income of the Gunung Kawi Tourism Object in Sebatu Village is good. management of the Gunung Kawi Tourism Object, Sebatu Village, availability and accessibility of documents, there are already documents used in the revenue management mechanism for the Gunung Kawi Tourism Object, Sebatu Village. Making reports and conveying them to the community in the Sebatu Traditional Village is not good. In this case, the report is presents verbally during a traditional village meeting. The openness of the process and regulatory framework that guarantees transparency is good, namely related to the openness of revenue management at the Gunung Kawi Tourism Object in Sebatu Village.